Cover Image, Volume 114, Number 1, January 2017. Issue 1 (January 2017) - Wu, Hsuan‐Chen; Quan, David N.; Tsao, Chen‐Yu; Liu, Yi; Terrell, Jessica L.; Luo, Xiaolong; Yang, Jen‐Chang; Payne, Gregory F.; Bentley, William E.
Abstract : Cover Legend The cover image, by William Bentley et al., is based on the Article Conferring biological activity to native spider silk: A biofunctionalized protein‐based microfiber, DOI:10.1002/bit.26065 .